An Overview of Asthma and COVID-19: Protective Factors Against SARS-COV-2 in Pediatric Patients - Liuzzo Scorpo, Maria; Ferrante, Giuliana; La Grutta, Stefania (Frontiers in Pediatrics, 2021)
Coronavirus disease 2019 (COVID-19) is a global pandemic infectious disease caused by severe acute respiratory syndrome coronavirus SARS-COV-2. Abnormal innate immunity and cytokine storm are responsible for the syndrome. Apparently, asthmatic patients should have increased susceptibility for SARS-COV-2 infection due to a deficient antiviral immune response and the tendency for disease exacerbation elicited by common respiratory viruses. Anyway, some studies have suggested that asthma is not a risk factor in COVID-19 patients. Therefore, in asthmatic patients some potential protective mechanisms against SARS-COV-2 have been hypothesized, like type 2 immune response, number of eosinophils, overproduction of mucus, and asthma treatment. In this mini-review, we will describe the current literature regarding potential protective factors against COVID-19 in asthmatic children based on the available evidence at this time.